Prognostic Significance of Circulating and Endothelial Progenitor Cell Markers in Type 2 Diabetic Foot - Sambataro, Maria; Seganfreddo, Elena; Canal, Fabio; Furlan, Anna; del Pup, Laura; Niero, Monia; Paccagnella, Agostino; Gherlinzoni, Filippo; dei Tos, Angelo Paolo (International Journal of Vascular Medicine, 2014)
Objective. We studied circulating precursor cells (CPC) in type 2 diabetes mellitus (T2DM) with neuropathic foot lesions with or without critical limb ischemia and relationships between endothelial precursor cells (EPC) and peripheral neuropathy. Methods and Subjects. We measured peripheral blood CD34, CD133, and CD45 markers for CPC and KDR, CD31 markers for EPC by citofluorimetry and systemic neural nociceptor CGRP (calcitonin gene related protein) by ELISA in 8 healthy controls (C) and 62 T2DM patients: 14 with neuropathy (N), 20 with neuropathic foot lesions (N1), and 28 with neuroischemic recent revascularized (N2) foot lesions. Timing of lesions was: acute (until 6 weeks), healed, and not healed. Results. CD34+ and CD133+ were reduced in N, N1, and N2 versus C, and CD34+ were lower in N2 versus N1 (P=0.03). In N2 CD34+KDR+ remain elevated in healed versus chronic lesions and, in N1 CD133+31+ were elevated in acute lesions. CGRP was reduced in N2 and N1 versus C (P<0.04 versus C 26±2 pg/mL). CD34+KDR+ correlated in N2 with oximetry and negatively in N1 with CGRP. Conclusions. CD34+ CPC are reduced in diabetes with advanced complications and diabetic foot. CD34+KDR+ and CD31+133+ EPC differentiation could have a prognostic and therapeutic significance in the healing process of neuropathic and neuroischemic lesions.